BENTUK PEMANFAATAN AIR BERBASIS TRADISI LOKAL, STUDI ETNOHIDROLOGI DI NEGERI HUKURILA, KOTA AMBON - Nurna Latupono; Bokiraiya Latuamury; Wilma N. Imlabla (PT. BARRINGTONIA ASIATICA LESTARI, 2026)
The availability of clean water in coastal and small island areas has become an increasingly complex challenge due to climate change and growing community demands. Hukurila Village, South Leitimur District, Ambon City, is one of the communities that continues to maintain a local wisdom-based water management system. This study aimed to analyze the local wisdom-based water management system, identify the socio-cultural factors influencing its implementation, and evaluate its role in supporting sustainable water resource management. A qualitative approach with a case study design was employed. Data were collected through in-depth interviews with 30 respondents, participatory observation, and document analysis, and were subsequently analyzed using thematic analysis. The findings revealed that water management in Hukurila is centered on three main practices: traditional wells (ai lounusa), rainwater harvesting, and sasi water. Traditional wells serve not only as a source of domestic water but also as a cultural and spiritual asset that strengthens social cohesion within the community. Rainwater harvesting functions as an adaptive strategy to cope with seasonal variability while reducing dependence on groundwater, whereas sasi water serves as a socio-ecological regulatory mechanism that supports the sustainability of water resources through collectively observed customary rules. The effectiveness of this system is reinforced by the values of pela gandong, pamali, mutual cooperation (gotong royong), the authority of the saniri negeri (customary council), and the active role of women in household water management. This study concludes that local wisdom plays a significant role in promoting sustainable water resource management and provides valuable insights for developing community-based water management policies in coastal and small island regions.